Working Papers in Sport & Leisure Commerce
The purpose of the Working Papers in Sport & Leisure Commerce is to provide an occasional outlet for scholarly works in progress that contribute to a body of knowledge consistent with the mission of the Bureau of Sport and Leisure Commerce. Focusing on an improved understanding of the cultural and material production, promotion, and consumption of sport and leisure in the urban context, contributions are encouraged from both traditional academic disciplines and fields of professional endeavor. In particular, these published works should stimulate dialogue in new ideas and will engage current theoretical debates. Moreover, it is expected that this series of Working Papers will cultivate critical, extra-disciplinary analysis and will reflect a wide range of research modalities.